Effect of Screw Rotation Speed on Mechanical Properties and Morphology of Abs/Mcc Composites - Irvian Adhana; Dharu Feby Smaradhana; Dody Ariawan; Wijang Wisnu Raharjo; Burhanuddin Yusuf (Mekanika: Majalah Ilmiah Mekanika, 2023)
Acrylonitrile Butadiene Styrene (ABS) polymer can be modified to increase strength against resistance, toughness, and heat resistance by adding Microcrystalline Cellulose (MCC) as a reinforcement to ABS composites. Extrusion is one of the established methods of polymer processing with filler and consequently disperses filler inside the polymer. Different speed shows different behaviour of filler dispersion. Therefore, this study was conducted to know the effect of extruder screw speed variations on the mechanical, physical, and thermal stability of ABS/MCC composites. The compositions used in producing ABS/MCC composites were 96% for ABS and 4% for MCC. The production process used screw extruder speed variations of 10 rpm, 15 rpm, and 20 rpm. ABS/MCC composite in the barrel and hot press used 160 °C for the temperature process. The highest tensile strength was obtained at 10 rpm variation for 14.2 MPa. Increasing the speed of the extruder screw caused a decrease in MCC content attached to ABS which reduced the mechanical strength. ABS/MCC composite density value decreased with the increased extruder speed, as evidenced by the increasing number of voids formed based on Scanning Electron Microscopy (SEM) testing.